Employee‟s Perception on Human Resources Practices on Employees in Hotel Industry: Examining the Impact of HR Practices on Employee Engagement in the Hotel Industry (Journal of Advances and Scholarly Researches in Allied Education, 2021)
A high-quality service industry, the hotel sector relies heavily on its employees, and the qualityof service is what drives hotel performance. As a result, this study examines how hotel workers evaluatetheir company's HR policies and how it affects their job engagement. Moreover, it attempts to determine ifthe link is mediated by the perceptions of organizational support that people have. There are a largenumber of women working in the hotel sector, yet there is still a significant gender gap. As they gothrough the ranks, the gender gap widens even further. Study participants who had a college degreewere shown to be more engaged at work than those who received no education. There was a strongcorrelation established between the level of work engagement and a person's position within a company.It was shown that a highly engaged workforce may be achieved if HR strategies are centered on theneeds of employees and put employees first. Managers' HR policies should make workers see them as ameans of assistance rather than only as a means of administration.